Knowledge and Job Opportunities in a Gender Perspective: Insights from Italy - Cipollone, Angela; Corsi, Marcella; D’Ippoliti, Carlo (Panoeconomicus, 2011)
The paper proposes an enlargement of the traditional notion of human capital, by conceptualising knowledge in a comprehensive and multidimensional way. In our empirical approach, knowledge encompasses several formal and informal skills, to complement the mainstream view narrowly concerned with education and on-the-job training. Our results for Italy point out that despite much rhetoric about the reduction (or even the reversal) of gender gaps in education, women often lack the main skills and competencies that can profitably be deployed in the labour market. Unsurprisingly, in Italy women’s accumulation of labour market experience is mostly hindered by unpaid housework burdens. However, when adopting an extensive definition of knowledge these activities may be regarded as a source of relevant knowledge. Yet, they do not seem to be positively valued by the market, either in terms of employability or in terms of wages, thus calling for a serious rethinking of the role of knowledge in shaping men’s and women’s economic opportunities. Key words: Definition of knowledge, Gender imbalances, Critique of human capital. JEL: J24, J16, B54.